Low-temperature plasma catalysis for VOCs control: Mechanistic insights and hybrid strategies - Junhui Li; Yuan Liu; Zhencheng Xing; Yide Jiang; Zichen Xu; Xuebin Lu; Yifei Sun; Yong Yin (Environmental Research, 2026)

Corrigendum to “Fluoride-induced male reproductive toxicity: Dual-tissue pyroptosis in the gut-testis axis mediated by inflammatory cytokines”, J. Hazard. Mater. (2026) 142537 - Shu Niu; Yuhui Du; Bin Liu; Zichen Feng; Guoqing Wang; Chunxiang Li; Yan Wang; Qing Sun; Fangfang Yu; Guoyu Zhou; Yue Ba (Journal of Hazardous Materials, 2026)

Fluoride-induced male reproductive toxicity: Dual-tissue pyroptosis in the gut-testis axis mediated by inflammatory cytokines - Shu Niu; Yuhui Du; Bin Liu; Zichen Feng; Guoqing Wang; Chunxiang Li; Yan Wang; Qing Sun; Fangfang Yu; Guoyu Zhou; Yue Ba (Journal of Hazardous Materials, 2026)

Synergistic inversion of maize leaf chlorophyll using multi-source remote sensing data - Shaoping Sun; Jixuan Yan; Guang Li; Zichen Guo; Wenning Wang; Qiang Li; Kejing Cheng; Xuchun Li; Jiaqin Yuan; Changbo Wu (Irrigation Science, 2026)

Electric-field-driven ultra-fine fibres (EDF): A sustainable and intelligent platform for future food packaging - Jun-Hu Cheng; Kai Zhang; Zichen Li; Da-Wen Sun (Trends in Food Science & Technology, 2026)

Efficient persulfate activation via a novel layered porous biochar enhanced with nano-zero-valent iron loading and synergistic sulfidation modification: Performance and mechanism - Lei Shen; Zichen Qin; Yuanding Shi; Yan Li; Pengyao Guo; Jinwei Zhang; Yijun Shen; Chun Yang; Yuchen Zeng; Dongxiao Sun; Zhiqiang Dong; Lei Ding (Journal of Water Process Engineering, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Spring extreme heat in the Indochina Peninsula enhances the prediction skill of summer precipitation in Central China - Yihua He; Wei Lou; Cheng Sun; Menghao Dong; Zichen Song; Linfeng Shi; Yibing Tong (Atmospheric Research, 2026)

Seasonal dynamics of Gulf Stream–Kuroshio SST coupling: the role of hemispheric atmospheric teleconnections - Menghao Dong; Cheng Sun; Linfeng Shi; Wei Lou; Zichen Song; Yihua He; Yibing Tong (Climate Dynamics, 2026)

Efficacy of alpha-lipoic acid in mitigating neuropathic pain: mechanistic insights and therapeutic implications - Daosong Dong; Yanbin Sun; Qingqing Sui; Zichen Zhao; Hong Ma; Kai Li; Xue Yu (Inflammopharmacology, 2026)

Changes in persistent anticyclonic circulation across Eurasian continent and its linkage with extreme heatwaves - Yibing Tong; Cheng Sun; Wei Lou; Menghao Dong; Linfeng Shi; Zichen Song; Yihua He (Global and Planetary Change, 2026)

Livestock manure-based organic fertilization facilitates the transmission of antibiotic resistance genes across the soil-onion continuum: A significant contribution from root exudates - Zixuan Zhao; Bin Luo; Tao Cao; Tongtong Bai; Yifan Sun; Hengrui Liu; Li Zhang; Jun Xie; Jun Wang; Huakang Li; Zichen Duan; Zixuan Gao; et al. (Soil Biology and Biochemistry, 2025)

Tracing toxic pollutants in coastal urban atmosphere: A case study on the particle-size distribution, sources, and health risks of PCDD/Fs, PCBs, PAHs, and substituted PAHs - Zhangpeng Guo; Shuai Sun; Rong Cao; Nan Jiang; Naibing Liang; Zichen Wang; Jiasen Guo; Minzhen Li; Xing Liu; Ningbo Geng; Jiping Chen (Journal of Hazardous Materials, 2025)

Limosilactobacillus reuteri FN041 alleviates cow's milk β-lactoglobulin–induced food allergy through immune modulation and gut microbiota remodeling - Renqiang Yu; Weijia Li; Zhou Zhou; Yue Yin; Zichen Luo; Ce Qi; Shanyu Jiang; Xiaoqing Chen; Danni Ye; Jin Sun (Food Bioscience, 2025)

Hetero-structured hydrogel with transition layer: Achieving synergistic sensing-actuating integration for intelligent ship - Bingchen Zhou; Tianzong Jiang; Yanqi Yin; Zewei Sun; Zichen Lu; Shili Gai; He Ding; Piaoping Yang (Chemical Engineering Journal, 2025)

Abrupt vapor pressure deficit changes over Northeast Asia during 1990s linked to combined Mediterranean-Pacific SST shifts - Zichen Song; Cheng Sun; Dong Xiao; Menghao Dong; Wei Lou; Linfeng Shi (Atmospheric Research, 2025)

Electro-oxidation of lincomycin and human pathogenic bacteria using carbon-supported lanthanide derivatives anodes: Accelerating wastewater remediation - Jia Wang; Yihang Hu; Tao Cao; Zichen Duan; Zixuan Zhao; Yifan Sun; Jie Gu; Xiaojuan Wang (Journal of Environmental Management, 2025)

Global teleconnection of concurrent dry and wet events revealed by climate network - Menghao Dong; Cheng Sun; Wei Lou; Linfeng Shi; Zichen Song; Yihua He; Yibing Tong (Climate Dynamics, 2025)

Mechanism insight into sulfidated nano zero-valent iron/biochar activated persulfate for highly efficient degradation of p-chloroaniline - Jingchun Yan; Zihan Guo; Yuyuan Sun; Zichen Yan; Rui Liu; Yudong Chen; Jing Song (Chemosphere, 2025)

Selection and applications of electrocatalysts for electrochemical anodizing oxidation of emerging contaminants in water: A review - Jia Wang; Yihang Hu; Tao Cao; Zichen Duan; Zixuan Zhao; Yifan Sun; Jie Gu; Xiaojuan Wang (Chemical Engineering Journal, 2025)

Novel colorimetric-fluorescent dual-mode biosensing platform for detecting acetylcholinesterase and screening acetylcholinesterase inhibitors based on trimetallic nanozymes - Meie Zheng; Mingxing Liu; Fei Ma; Zichen Song; Hongda Zhu; Huiling Guo; Hongmei Sun (Chemical Engineering Journal, 2025)

Human milk-derived Limosilactobacillus reuteri FN041 ameliorates DSS-induced colitis by remodeling gut microbiota and metabolites in mice - Zichen Luo; Jin Sun; Ji Liu; Ping Yu; Danni Ye; Ce Qi; Xiaoqing Chen; Renqiang Yu (Food Bioscience, 2025)

Efficient catalytic oxidation of xylose to formic acid with the oxygen vacancies of CeO2 promoted the vanadium catalysts anchored on biochar - Shuxia Wei; Tong Sun; Wenbo Liao; Zhili Li; Zichen Li; Yong Sun (Chemical Engineering Journal, 2024)

Establishment of a semi-continuous scale-down clone screening model for intensified perfusion culture - Tao Sun; Yu Zhang; Hengrui Liang; Wenjing Fang; Zichen Qian; Kee Wee Tan; Junjie Li; Xiang Zheng; Mingyue Fang; Hang Zhou; Weichang Zhou; Sam Zhang (Biotechnology Letters, 2024)

Metagenomic insights into the mechanism of sophorolipid in facilitating co-anaerobic digestion of mushroom residues and cattle manure: Functional microorganisms and metabolic pathway analysis - Zixuan Zhao; Fei Wu; Jian Sun; Lan Jiang; Yiran Zhang; Jun Wang; Zhijiang Shao; Yifan Sun; Zichen Duan; Yu Zhang; Tongtong Bai; Yucheng Liu; et al. (Journal of Environmental Management, 2024)

The removal of antibiotic resistance bacteria and genes and inhibition of RP4 plasmid-mediated conjugative transfer by citric acid chelated Fe(II) catalyzing peroxymonosulfate systems: Performance and mechanisms - Hengrui Liu; Lu An; Zixuan Gao; Zichen Duan; Bin Luo; Yifan Sun; James M Tiedje; Jie Gu; Xiaojuan Wang (Chemical Engineering Journal, 2024)

Rapid-response electrochromic devices with self-wrinkling polyaniline for enhanced infrared emissivity modulation - Yike Zhang; Dongqi Liu; Zichen Ren; Wenchao Liu; Bo Wang; Shanshan Song; Tingting Hao; Lei Xu; Haoyu Ji; Jiawu Sun; Leipeng Zhang; Yao Li (Chemical Engineering Journal, 2024)

Source identification of nitrate in groundwater of an agro-pastoral ecotone in a semi-arid zone, northern China: Coupled evidences from MixSIAR model and DOM fluorescence - Anqi Chen; Yao Du; Zichen Wang; Xiaoliang Sun; Rui Xu; Yaojin Xiong; Liangping Yang; Junting Liu; Yiqun Gan (Applied Geochemistry, 2024)

Capsaicin reduces blood glucose and prevents prostate growth by regulating androgen, RAGE/IGF-1/Akt, TGF-β/Smad signalling pathway and reversing epithelial-mesenchymal transition in streptozotocin-induced diabetic mice - Hui Sun; ZiTong Wang; BingHua Tu; ZiChen Shao; YiDan Li; Di Han; YinJie Jiang; Peng Zhang; WeiChang Zhang; YunYan Wu; XiaoMing Wu; Chi-Ming Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Unravelling spatiotemporal patterns in global sea surface temperatures with dynamic mode decomposition - Menghao Dong; Cheng Sun; Tian Wei; Zijing Guo; Wei Lou; Zichen Song; Linfeng Shi (International Journal of Climatology, 2024)
Extracting global sea surface temperature (SST) patterns is essential for understanding climate variability in both regional and global perspective. Traditional methods, limited by assumptions of orthogonality, hinder our ability to fully capture the dynamics of global SST, particularly in the complex Pacific basin. This study introduces dynamic mode decomposition (DMD), a powerful method from fluid dynamics, to extract global SST patterns since 1900. Our analysis shows that DMD successfully captures well‐known patterns like global warming and the Atlantic Multidecadal Oscillation (AMO). More importantly, it reveals three Pacific SST modes that are spatially non‐orthogonal but exhibit distinct characteristics. Spectral analysis shows that these Pacific modes have distinct periodicities: Pacific Multi‐decadal Mode (PMDM, ~50 years), Quasi‐decadal Mode (PQDM, 8–16 years) and Interannual Mode (PIAM, 2–8 years). This highlights DMD's strength in not only capturing known patterns but also separating modes with similar spatial features but unique dynamics. Further analysis reveals significant differences in their impacts on global air temperature. During positive phases, all three modes induce tropical warming, with PIAM exerting the strongest influence and PMDM the weakest. In the Northern Hemisphere, both PQDM and PIAM drive mid‐latitude cooling and high‐latitude warming, with a more pronounced effect from PQDM. PMDM, in contrast, triggers widespread cooling across the Northern extratropics. In the Southern Hemisphere, PMDM's influence on temperature exhibits a distinct latitudinal banding pattern. PIAM and PQDM, on the other hand, exhibit a regionalized impact, primarily concentrated in the Amundsen and Ross Seas, with PQDM's influence extending to the Antarctic continent.

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Healable and multi driving mode soft actuator enabled by disulfide-bonded liquid crystal elastomers - Shuoning Zhang; Zichen Wang; Jianying Zhang; Jiale Liu; Chang Sun; Shengyu Qin; Yunxiao Ren; Lanying Zhang; Wei Hu; Huai Yang (Chemical Engineering Journal, 2024)

Spatio-temporal variation and drivers of blue carbon sequestration in Hainan Island, China - Zichen Li; Ling Liu; Chuhan Sun; Xiaoyang Shan; Hongwei Zhao (Marine Environmental Research, 2024)

Interhemispheric propagation of seasonal sea surface temperature fluctuations over the western Pacific in CMIP6 - Tian Wei; Cheng Sun; Zijing Guo; Wei Lou; Zichen Song; Linfeng Shi; Menghao Dong (International Journal of Climatology, 2024)
Interannual sea surface temperature (SST) variability in the western Pacific is a critical research topic in climate change, as it can significantly impact regional and global weather patterns. Previous observational studies have shown that SST in the southwestern Pacific (SWP) can effectively serve as a precursor signal for SST in the western tropical Pacific (WTP). In this study, we evaluate and compare the modelling capabilities of 32 CMIP6 models to simulate the relationship between SWP and WTP SST. The results indicate that while some CMIP6 models can simulate the spatial connection and physical processes between the SWP and WTP, there are significant intermodel differences. Specifically, the models that best simulate the cross‐equatorial propagation of SWP SST anomalies are those that accurately simulate the cross‐equatorial wind anomalies induced by SWP SST anomalies, highlighting the key role of wind‐evaporation‐SST feedback in SST propagation. Further analysis reveals that the intermodel spread in cross‐equatorial SST propagation is attributable to model biases in simulating climatological SST and wind speed. Models with warm climatological equatorial SST and strong wind speeds provide favourable conditions for the cross‐equatorial propagation of SWP‐related SST anomalies towards the north. Warm SST and strong inter‐season wind speeds near the equator facilitate the northward propagation of the SWP warm signal, leading to increased warming in the WTP.

A novel competitive fluorescence colorimetric dual-mode immunosensor for detecting ochratoxin A based on the synergistically enhanced peroxidase-like activity of AuAg NCs-SPCN nanocomposite - Chenxi Ke; Yu Wu; Zichen Song; Meie Zheng; Hongda Zhu; Huiling Guo; Hongmei Sun; Mingxing Liu (Food Chemistry, 2024)

Locally π-π conjugated polyimide cured triglycidyl isocyanurate epoxy resin with enhanced dielectric polarization and microwave absorption performance for X and Ku bands - Zichen Xu; Kexin Zhang; Yajie Cheng; Xiping Sun; Haofan Ren; Hao Wei; Qiang Wang; Lin Wang; Zhijia Zhang; Guojun Wang (Chemical Engineering Journal, 2024)

Low-frequency mechanical energy in the environment for energy production and piezocatalytic degradation of organic pollutants in water: A review - Xiaxia Chen; Jingxue Wang; Zichen Wang; Hongwei Xu; Chao Liu; Bingjie Huo; Fanqing Meng; Yinglong Wang; Chaoyue Sun (Journal of Water Process Engineering, 2023)

Research progress of PVDF based piezoelectric polymer composites in water pollution remediation - Chao Liu; Hongwei Xu; Bingjie Huo; Jingxue Wang; Zichen Wang; Xiaxia Chen; Fanqing Meng; Chaoyue Sun; Yinglong Wang (Journal of Water Process Engineering, 2023)

Oridonin attenuates the progression of atherosclerosis by inhibiting NLRP3 and activating Nrf2 in apolipoprotein E-deficient mice - Lei Wang; Xiaoqi Zhao; Jiawen Ding; Yutong Liu; Han Liu; Lei Zheng; Hongting Zhao; Zichen Sun; Kuanyu Li; Jing Cai; Tong Qiao (Inflammopharmacology, 2023)
Oridonin, a well-known traditional Chinese herbal medicinal product isolated from Isodon rubescens (Hemsl.) H.Hara, has many potential properties, including anti-inflammatory and antioxidant activities. However, there is no evidence whether oridonin have a protective effect on atherosclerosis. This study focused on the effects of oridonin on oxidative stress and inflammation generated from atherosclerosis. The therapeutic effect on atherosclerosis was evaluated by intraperitoneal injection of oridonin in a high-fat fed ApoE −/− mouse model. We isolated mouse peritoneal macrophages and detected the effect of oridonin on oxidized low-density lipoprotein-induced lipid deposition. Oil red O staining, Masson's staining, dihydroethidium fluorescence staining, immunohistochemical staining, western blotting analysis, immunofluorescence, enzyme-linked immunosorbent assay and quantitative real-time PCR were used to evaluate the effect on atherosclerosis and explore the mechanisms. Oridonin treatment significantly alleviated the progression of atherosclerosis, reduced macrophage infiltration and stabilized plaques. Oridonin could significantly inhibit inflammation associated with NLRP3 activation. Oridonin significantly reduced oxidative stress by blocking Nrf2 ubiquitination and degradation. We also found that oridonin could prevent the formation of foam cells by increasing lipid efflux protein and reducing lipid uptake protein in macrophages. Oridonin has a protective effect on atherosclerosis in ApoE −/− mice, which may be related to the inhibition of NLRP3 and the stabilization of Nrf2. Therefore, oridonin may be a potential therapeutic agent for atherosclerosis.

A Data-Driven Model for Ice-Breaking Resistance of Structure Based on Non-Smooth Discrete Element Method and Artificial Neural Network Method - Zhe Sun; Yongjin Qiu; Biye Yang; Zichen Jia; Guiyong Zhang; Zhi Zong (Journal of Marine Science and Engineering, 2023)
In this paper, a data-driven model based on the Non-smooth Discrete Element Method (NDEM) and Artificial Neural Network Method (ANN) is proposed for the computation of the ice-breaking resistance of the structure. The idea of so-called “meta-modelling”, which means establishing an Artificial Neural Network (ANN) model based on a pre-computed ice failure database to avoid the time-consuming direct resolving of the ice fracture process, was integrated in the non-smooth discrete element method (NDEM). The developed model was validated by simulating the ice-breaking process of the cone structure, and the computational results match well with the experimental ones in the literature. After that, the effects of various parameters on the ice-breaking resistance were analyzed by the developed model. It was found that the factors that have great influence on the resistance of cone structure in level ice condition are the cone angle, navigation velocity and ice thickness.

Effects of adsorption characteristics of different amendments on heavy metals (Pb, Zn, and Cd) - Yaqian Li; Jiawei Ma; Mohammad Shafi; Yefang Sun; Yongqing Li; Zhenhua Chen; Zichen Xiang; Gaoqi Jin; Bin Zhong; Zhengqian Ye; Dan Liu (Journal of Soils and Sediments, 2020)

Genome-wide identification and expression analysis of the CLC superfamily genes in tea plants (Camellia sinensis) - Anqi Xing; Yuanchun Ma; Zichen Wu; Shouhua Nong; Jiaojiao Zhu; Hua Sun; Jing Tao; Bo Wen; Xujun Zhu; Wanping Fang; Xiaocheng Li; Yuhua Wang (Functional & Integrative Genomics, 2020)

Epigenetic Signature of Chronic Cerebral Hypoperfusion and Beneficial Effects of S-adenosylmethionine in Rats - Xiangmei Wu; Jing Sun; Xiaowen Zhang; Xiaona Li; Zichen Liu; Qinglin Yang; Liang Li (Molecular Neurobiology, 2014)